COOPERATION BETWEEN CENTRAL ASIAN COUNTRIES IS A GUARANTEE OF PEACE AND DEVELOPMENT - Ikramov Ravshan Aktamovich; Normatov Otabek Maxamatjonovich (Bright Mind Publishing, 2026)
This article, using statistical analysis and examples, demonstrates the importance of cooperation between Central Asian countries. In particular, it examines the importance of further strengthening ties with the independent states of Central Asia, which is one of the main directions of the foreign policy of the Republic of Uzbekistan.
Keywords: Central Asia, foreign policy of the Republic of Uzbekistan, independent states, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, regional integration.